Giant Cell Tumor of the Proximal Femur with Pathological Fracture of Femoral neck - Gagandeep Gupta; Abhishek Singh; Shivang Kala; Akhilesh Saini; Shristi Singh; Sopan Shende (Journal of Orthopaedic Case Reports)
Introduction: Giant cell tumor (GCT) of bone is a locally aggressive, benign neoplasm, accounting for approximately 20% of all bone tumors. While the distal femur and proximal tibia are the most common locations for GCTs, with the majority arising in the epiphyseal regions, their occurrence in the proximal femur is relatively rare, representing only 5.5% of cases. These tumors pose significant management challenges due to their tendency to cause pathological fractures, aggressive local behavior, and involvement of critical weight-bearing bones. Effective treatment requires careful consideration of both oncological control and functional preservation. Case Report: A 43-year-old male presented with a GCT in the proximal femur, complicated by a pathological fracture of the femoral neck. Given the tumor’s size and location, the patient underwent extended curettage (EC) to remove the tumor, followed by internal fixation with a dynamic hip screw and the application of bone cement for additional stabilization. Post-operative monitoring, including clinical and radiological assessments, showed favorable results. After a 12-month follow-up period, the patient had no signs of recurrence, and his functional and radiological outcomes were excellent, with restored mobility and the ability to bear weight on the affected limb. Conclusion: This case emphasizes the need for a tailored treatment strategy when managing GCTs of the proximal femur, particularly in resource-limited settings. The combination of EC, internal fixation, and bone cement was effective in achieving both oncological control and functional recovery. Long-term follow-up remains essential to monitor for recurrence and to ensure the integrity of the fixation device. The positive outcomes in this case highlight the potential for successful management of GCTs in challenging anatomical locations with appropriate surgical intervention and post-operative care.